Influence of post-condensation on the crystallization kinetics of PA12: From virgin to reused powder. (26th June 2019) - Paolucci, F.; van Mook, M.J.H.; Govaert, L.E.; Peters, G.W.M.
Abstract: The effect of prolonged storage at elevated temperatures on the isothermal crystallization kinetics of Polyamide 12 (PA12), the most used polymer in selective laser sintering (SLS), has been studied by means of Flash DSC experiments. The experimental results are described and modelled with a full multi phase crystallization model which allowed us to estimate the growth and nucleation kinetics for every PA12 crystal phase. Virgin PA12 powder has been annealed at different temperatures for different times to quantify the molecular weight evolution due to post condensation. To check the effect of thermal treatments on the final viscosity, rheology measurements have been carried out. We show that thermal annealing results in a significant increase in molecular weight and viscosity which lead to a reduction of the crystallization rate in a limited temperature range. At very low temperature the crystallization kinetics, expressed in terms of peak-time of crystallization, appears to be independent on the annealing treatment while in the temperature range between 100 ∘ C and 150 ∘ C a significant rate reduction is observed. We demonstrate that the crystallization kinetics in this temperature range is governed by the crystal growth process, i.e. the increase in molecular weight due to post-condensation causes a reduction of the growth rate of the main crystalline phases of PA12, namely α ' and γ -phase. Similar to the low temperature crystallization, at temperature higher than 150 ∘ C the annealing does not noticeably affect the growth rates and the crystallization kinetics of virgin and annealed PA12 overlap. These results can provide a better insight of the effect of reusing PA12 powder in the SLS process. Graphical abstractptninpH: Image 1 Highlights: The effect of prolonged storage at relatively high temperature on the crystallization kinetics of polyamide 12 (PA12) has been studied by using Flash DSC. The results were implemented in a multi-phase crystallization model that allows us to calculate growth and nucleation rates for different PA12 crystal phases. It is shown that thermal annealing results in a significant increase in molecular weight due to post condensation and this reduces the crystallization rate. There is no noticeable effect on the crystallization kinetics at low (below 90°C) and high (above 150°C) temperature range. The results can provide a better insight of the effect of reusing PA12 powder the SLS process.